A practical guide to teaching music in the secondary school [ - Evans, Julie , 1958-; Philpott, Chris , 1956- (Routledge teaching guides, 2009)
Offers guidance and ideas for student teachers, mentors and practising teachers who want to develop their music teaching. This title helps you understand the developments and explore the possibilities for teaching and learning. It explores musical learning through placing pupils at the centre of a musical experience